The Utilization of Audiovisual Learning Media in Enhancing the Learning Interest of SB Kepong Children - Nur Maratun Solihah; Indriwati Wahyuni; Niken Cahya Mamonto; Eko Purnomo (International Conference on Education for All, 2023)
Education is a crucial aspect worldwide, including in Indonesia. The country is making significant efforts to enhance the quality of education for its citizens, including those living abroad. One notable example is Sanggar Belajar Kepong, established a year ago by the Special Branch of Muhammadiyah Malaysia (PCIM). Located in Kepong, Kuala Lumpur, Malaysia, this center aims to nurture the potential and intelligence of young Indonesians living abroad. To achieve this goal, innovation is key, and the center strives to make learning engaging and enjoyable for its students. One effective method used is incorporating audiovisual technology as an educational tool. Through the Community Service Program (KKN-KI) at SB Kepong, this method has been successfully implemented, resulting in a positive impact on SB Kepong students, who have become more enthusiastic and interested in learning.